Understanding The Factors That Influence Consumer Continuous Intention To Use E-Wallet In Malaysia - Wong, Chi Ying; Pakir Mohamed, Mohamed Ismail (Research in Management of Technology and Business, 2021)
Abstract: Digital economy has changed the way people doing business. Cashless transaction via electronic media is the global trend achieving a cashless society. The government rolling out the E-Tunai Rakyat and e-Penjana initiatives for the E-wallet users have boosted up the usage of E-wallet. Besides, the emerging of coronavirus also has raised the awareness of contactless payment in many countries including Malaysia. The objectives of the research are to determine the reasons that Malaysian consumers sign up for E-wallet and the factors that influence the users’ continuous intention to use E-wallet after claiming the government E-wallet initiatives. The TAM model has been used. A total of 351 sets of data were collected from Ipoh, Perak through an online survey. SPSS Data analysis software has been used to analyze the collected data. The findings show that the majority of E-wallet users strongly agree that they sign up for E-wallet because they want to claim the E-wallet initiatives which shows that the government strategies were effective. Spearman’s rho correlation was applied to analyze the factors that influence the continuous intention to use E-wallet. The results reveal PU, PEOU, PS, and PE are positively correlated with the users’ continuous intention. PEOU also positively correlated with the PU. The findings show that these factors significantly influence users’ continuous intention. Future study is suggested to research different states since this research only focused on Ipoh. Keywords: E-wallet, TAM model, E-wallet initiatives, Continuous Intention To Use